Educational Innovation in the Evaluation Processes within the Flipped and Blended Learning Models - Monserrath Yangari; Esteban Inga (MDPI AG, 2021)
Nowadays, several institutions and universities have employed Flipped and Blended Learning models in the educational context. Consequently, these models advance correctly in the classrooms; students become more able to build their knowledge and develop their skills with technological innovation that could be compared with studies based on technological achievements and accessible data Tics. Therefore, this article proposes educational innovation in the evaluation processes within the FL and BL learning models to ensure active and interactive education. In this work, a bibliometric analysis of 2000 scientific articles from the Web of Science and Scopus databases has been carried out, thus making it possible to identify countries and universities with constant and relevant use of these learning models, as well as a comparison with these databases of articles, citations and their global impact. On the other hand, a survey was conducted with 41 teachers of different subjects and 385 students from elementary school to high school using the Likert scale. The questions were represented in perception values with their respective analysis of results and evaluations about these learning models, technological resources, flexible curriculum, learning before class, autonomous learning, and future professional competencies, which will help us know the existing motivation between them.